Fracture toughness of alumina filler filled glass fabric reinforced epoxy composites. (2021) - Sandeep, B.; Suresha, B.; Divakar, H.N.
Abstract: Micron sized alumina particles (≤10 µm) are incorporated between the plies of a conventional glass fabric reinforced epoxy (GE) composite to improve the fracture toughness ( KIC ). The influence of the alumina filler content (0, 7.5, and 10 wt%) on KIC are investigated. These composites are prepared by hand layup assisted by the vacuum bagging method. The prepared composites are evaluated for KIC at room temperature, elevated temperature (100 °C) and at cryogenic temperature (−15 °C). The KIC test was conducted utilizing single notched edge bend specimen under mode I according to ASTM D5045 standard. The test results indicated that KIC of GE is improved by addition of alumina particles. Furthermore, these composites maintained higher KIC at −15 °C and decreased significantly at elevated temperature. The maximum KIC is recorded at particle loading of 10 wt% GE hybrid composite.